2015
DOI: 10.2298/ciceq140212020l
|View full text |Cite
|
Sign up to set email alerts
|

PM and CO2 variability and relationship in the different school environments

Abstract: Article Highlights• Diurnal variation of PM, CO 2 and NO 2 in classroom • PM, CO 2 and NO 2 concentrations during heating and non-heating period • Strong correlation between PM and carbon dioxide CO 2 concentrations • Management strategy for controlling of PM and CO 2 levels inside the schools is needed Abstract Indoor air quality (IAQ) is very important for children health and well-being, since children are particularly vulnerable and sensitive to the presence of air pollutants. This study was performed in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(38 reference statements)
3
10
0
1
Order By: Relevance
“…The authors reported that the main indoor air pollutant sources were those related to occupancy and settled dust: CO 2 and PM. Lazovic et al [30] assessed PM 10 , PM 2.5 , CO 2 , and NO 2 concentrations in two schools and identified a correlation between PM and CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the main indoor air pollutant sources were those related to occupancy and settled dust: CO 2 and PM. Lazovic et al [30] assessed PM 10 , PM 2.5 , CO 2 , and NO 2 concentrations in two schools and identified a correlation between PM and CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A high negative correlation was found between the temperature and the PM 2.5 concentration. In [36], Lazović et al detected high correlations between the CO 2 concentration and PM 2.5 and PM 10 in two schools in the non-heating period. They also revealed a correlation between the CO 2 concentration and relative humidity and indoor air temperature in their next study [37].…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve IAQ, several IAP mitigation measures were identified, based on the literature [ 8 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 38 , 39 ] and grouped hierarchically in 5 different types, from the less to the most expensive and complex: Type I—raising awareness; Type II—behavioural changes; Type III—changes in products/materials and places of activities; Type IV—technical and technological changes; Type V—structural changes. Detailed description of those measures can be consulted in Table S1 (Supplementary Materials) .…”
Section: Methodsmentioning
confidence: 99%
“…After observing high concentrations of indoor air pollutants, mainly particulate matter (PM), carbon dioxide (CO 2 ) and volatile organic compounds (VOC), several studies concluded that there is a pressing need to implement strategies to improve IAQ, through the implementation of measures to mitigate indoor air pollution (IAP): (i) the change of some behavioural habits, promoting efficient ventilation [ 8 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]; (ii) the improvement of cleaning actions [ 19 , 21 , 22 , 23 , 27 , 29 , 31 , 32 , 33 ]; (iii) the replacement of carpets and carpeted floors by smooth panels [ 27 , 33 ]; (iv) the adequacy of occupational density and promotion of more class breaks and outdoor activities [ 12 , 27 , 32 ]; and (v) structural measures such as the installation of air purifiers [ 33 ], the replacement of building materials, furniture and windows [ 25 , 34 ] and the replacement of the heating system [ 26 ].…”
Section: Introductionmentioning
confidence: 99%